Protocol for acquiring high-quality fresh mouse lung spatial transcriptomics data - Yujia Jiang; Yixin Li; Mengnan Cheng; Jiangshan Xu; Xiaoyu Wei; Chuanyu Liu (STAR Protocols, 2024)
Summary: Spatial transcriptomics analysis allows the examination of the biological characteristics and spatial distribution of individual lung cells at a single-cell resolution. However, due to the presence of cavities in the alveoli of the lungs, it is challenging to section them for spatial transcriptomics experiments. Here, we present a protocol for acquiring high-quality fresh mouse lung spatial transcriptomics data. We describe steps for lung perfusion, acquiring frozen slices, collecting cDNA from lung sections, and data analysis.For complete details on the use and execution of this protocol, please refer to Jiang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.